2017
DOI: 10.1016/j.ijcard.2017.06.109
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic reference ranges in older children and adolescents in sub-Saharan Africa

Abstract: BackgroundEchocardiographic reference ranges are important to identify abnormalities of cardiac dimensions. Reference ranges for children in sub-Saharan Africa have not been established. The aim of this study was to establish echocardiographic z-score references for Black children in sub-Saharan Africa.Methods282 healthy subjects aged 6–16 years (143 [51%] males) with no known history of cardiac disease were enrolled in the study in Harare, Zimbabwe between 2014 and 2016. Standard M-mode echocardiography was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Echocardiography measures for LV and right ventricular (RV) dimensions were normalized to body surface area calculated using Du Bois and Du Bois formula [ 17 ], and converted to z -scores using local references [ 18 ] and further compared with European published references among Caucasian children [ 19 ]. Local reference ranges were used as the primary basis for defining cardiac abnormalities in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography measures for LV and right ventricular (RV) dimensions were normalized to body surface area calculated using Du Bois and Du Bois formula [ 17 ], and converted to z -scores using local references [ 18 ] and further compared with European published references among Caucasian children [ 19 ]. Local reference ranges were used as the primary basis for defining cardiac abnormalities in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Only one study each was conducted in South America (Brazil) and Africa (Zimbabwe). Nine studies reported the race of children studied [ 6 , 8 , 9 , 19 , 23 , 25 , 33 , 38 , 39 ]. Sample sizes of the studies ranged from 95 to 9858.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reference ranges in children were, however, developed in European and North American (US populations) and mainly in Caucasians. Notably, there was only one study each from South America (Brazil) and Africa (Zimbabwe) and the latter was published very recently, implying that most African countries rely on Western references in clinical practice which may not accurately represent black African children [ 6 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…transpulmonary-thermodilution, thoracic bioimpedance-bioreactance, ultrasonography). Among them, echocardiography stands out as a method widely used and recommended in clinical practice [3][4][5]. However, different factors contribute to circumscribe the use of echocardiography to certain contexts and conditions, limiting its widespread use (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…for community-based epidemiological studies). Among those factors are: (1) physical (size) restrictions and cost of the devices, (2) operator-dependency and the need for a learning-curve, (3) inability to obtain adequate records in many subjects or conditions, (4) different acquisition approaches may affect measurement variability, (5) a relatively long period of time is required to complete a study and/or (6) ambulatory records or continuous monitoring of the variables cannot be obtained [6,7]. Pulse contour analysis (PCA) of blood pressure (BP) waveforms obtained non-invasively would enable estimating the SV, CO and CI [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%